2001
DOI: 10.1097/00004714-200110000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Dextroamphetamine for Cocaine-Dependence Treatment: A Double-Blind Randomized Clinical Trial

Abstract: A properly implemented agonist treatment regimen should improve retention and reduce illicit drug use. Cocaine-dependent subjects (N = 128) were enrolled in a 12-week randomized, double-blind, placebo-controlled trial. In the multistage dosing design, subjects initially received placebo (PBO) or 15 to 30 mg of dextroamphetamine sulfate, sustained-release capsules. At week 5, the dose doubled to 30 mg or 60 mg for active groups. Subjects attended the clinic twice a week, provided urine samples, obtained medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
224
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(252 citation statements)
references
References 19 publications
28
224
0
Order By: Relevance
“…Under these conditions, d-amphetamine produced a dose-dependent decrease in cocaine choice and a reallocation of responding to the food choice. These results closely parallel the results of a recent double-blind, placebo-controlled clinical study, which found that oral damphetamine (15-60 mg twice daily, or approximately 0.4-1.7 mg/kg/day) dose-dependently decreased measures of cocaine use in stimulant abusers (Grabowski et al, 2001). In that study, retention was highest at the intermediate doses of 15-30 mg/day, and the higher d-amphetamine doses produced undesirable effects, such as insomnia and muscle twitching, that decreased retention.…”
Section: Effects Of Treatment With Candidate Pharmacotherapiessupporting
confidence: 85%
See 1 more Smart Citation
“…Under these conditions, d-amphetamine produced a dose-dependent decrease in cocaine choice and a reallocation of responding to the food choice. These results closely parallel the results of a recent double-blind, placebo-controlled clinical study, which found that oral damphetamine (15-60 mg twice daily, or approximately 0.4-1.7 mg/kg/day) dose-dependently decreased measures of cocaine use in stimulant abusers (Grabowski et al, 2001). In that study, retention was highest at the intermediate doses of 15-30 mg/day, and the higher d-amphetamine doses produced undesirable effects, such as insomnia and muscle twitching, that decreased retention.…”
Section: Effects Of Treatment With Candidate Pharmacotherapiessupporting
confidence: 85%
“…Choice procedures are being used with increasing frequency to evaluate candidate pharmacotherapies in human studies (Haney et al, 1998(Haney et al, , 1999(Haney et al, , 2001Walsh et al, 2001), but to date, choice procedures have been used only sparingly for this purpose in preclinical research Balster, 1979, 1981). In the present study, the monoamine releaser damphetamine was tested as a candidate 'agonist' medication, because it produces many cocaine-like effects (Colpaert et al, 1979;Hoffman, 2001), and because several recent clinical studies reported promising results with d-amphetamine maintenance in the treatment of stimulant abuse (Fleming and Roberts, 1994;Charnaud and Griffiths, 1998;White, 2000;Grabowski et al, 2001). Flupenthixol was tested as a representative 'antagonist' medication, because it is a nonselective antagonist at D1 and D2 dopamine receptors that was reported to block some abuse-related effects of cocaine (Ettenberg et al, 1982;Baker et al, 1993) and that has also been evaluated as a treatment for cocaine dependence (Soyka and DeVry, 2000;Evans et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion is a DA and norepinephrine reuptake inhibitor that is an effective treatment to promote smoking cessation [180]. Dextroamphetamine causes release of DA (as well as norepinephrine and serotonin) and is an effective treatment for amphetamine abuse [181]. Finally, risperidone, a D 2 -receptor antagonist, has shown promise for the treatment of methamphetamine abuse [182], and aripiprizole, a partial D 2 agonist is a promising treatment for amphetamine abuse [183].…”
Section: Reviewmentioning
confidence: 99%
“…The other category of strategies consists of pharmacological approaches, such as maintenance on an agonist-based pharmacotherapy, and clinical trials have demonstrated efficacy of maintenance on the dopamine/norepinephrine vs serotonin-selective monoamine releaser d-amphetamine to decrease cocaine abuse (Grabowski et al, 2001(Grabowski et al, , 2004Mooney et al, 2009). However, interactions between behavioral and pharmacological approaches in the treatment of cocaine abuse are poorly understood and understudied.…”
Section: Introductionmentioning
confidence: 99%